FAKTOR-FAKTOR PENDORONG KONVERSI LAHAN SAWAH DI KABUPATEN BANTUL - Ayub Ayub; Bambang Pramudya Noorachmat; Muhammad Yanuar Jarwadi Purwanto (Universitas Lambung Mangkurat, 2022)
The increased population entails increased food production so that food can be securitized. The root cause of the food security problem is agricultural land use conversion. This study aimed to quantify the paddy field land-use conversion and analyze the driving factors of conversion in the Regency of Bantul. Spatial analysis methods were used based on the satellite image digitization technique and map stacking using ArcGIS software version 10.6; besides, a questionnaire was used to interview the farmers. The questionnaires were analyzed with descriptive statistical methods. The Spatial analysis shows that the Regency has experienced a conversion in its paddy field of 639 ha between 2010–2019. The study has identified that education level, age of farmers, land ownership, land prices, and the distance of rice fields to the road were the factors driving paddy field conversion in the Regency. The regency government needs to incentify the farmers who do not violate sustainable agricultural food land (LP2B). Immediately establish (LP2B) and periodically monitor the area of rice fields using satellite imagery data to know the existence and make appropriate policies.